Feasibility of Audio‐Computer‐Assisted Self‐Interviewing With Color‐Coding and Helper Assistance (ACASI‐H) for Hmong Older Adults. Issue 4 (21st April 2017) - Lor, Maichou; Bowers, Barbara J.
Abstract: Many older adult immigrants in the US, including Hmong older adults, have limited English proficiency (LEP), and cannot read or have difficulty reading even in their first language (non‐literate [NL]). Little has been done to identify feasible data collection approaches to enable inclusion of LEP or NL populations in research, limiting knowledge about their health. This study's purpose was to test the feasibility of culturally and linguistically adapted audio computer‐assisted self‐interviewing (ACASI) with color‐labeled response categories and helper assistance (ACASI‐H) for collection of health data with Hmong older adults. Thirty dyads (older adult and a helper) completed an ACASI‐H survey with 13 health questions and a face‐to‐face debriefing interview. ACASI‐H survey completion was video‐recorded and reviewed with participants. Video review and debriefing interviews were audio‐recorded and transcribed. Directed and conventional content analyses were used to analyze the interviews. All respondents reported that ACASI‐H survey questions were consistent with their health experience. They lacked computer experience and found ACASI‐H's interface user‐friendly. All used the pre‐recorded Hmong oral translation except for one, whose helper provided translation. Some Hmong older adults struggled with the color labeling at first, but helpers guided them to use the colors correctly. All dyads liked the color‐labeled response categories and confirmed that a helper was necessary during the survey process. Findings support use of oral survey question administration with a technologically competent helper and color‐labeled response categories when engaging LEP older adults in health‐related data collection. © 2017 Wiley Periodicals, Inc.